Why newborns die? A self-audit - Sagayaraj, Benjamin M.; Sharma, Nidhi; D. V., Lal (International Journal of Contemporary Pediatrics, 2016)
Background: A birth weight specific reduction in neonatal mortality has been noted in babies above 1000 gm. This has been attributed to intensive care management of high-risk pregnancies and new borns. A further decline in mortality can be accomplished by evidence based evaluation of high-risk therapies. This prospective study was conducted to evaluate the postnatal factors correlating with new born mortality. Apgar scores at birth have been correlated with deaths in low birth weight babies. In the present study we tried to correlate the presence of apnea, hyaline membrane disease, necrotizing enterocolitis and sepsis with neonatal mortality. Lethal Congenital malformations were also studied. It is a prospective consecutive enumerative study of all new borns weighing less than 2000 grams. Methods: The post natal course in the hospital including the presence of apnea, seizures, patent ductus arteriosus, intra ventricular hemorrhage, hyaline membrane disease, hyper bilirubinemia, necrotizing enterocollitis, duration of oxygen therapy and ventilator support were noted. Statistical analysis was done using Fisher Exact test. Results: There was a significant increase in mortality if the new born had low Apgar score, necrotizing enterocollitis, hyaline membrane disease, apnoea, sepsis or congenital malformations. Nursery biological risk score is a sensitive tool to predict new born mortality. Conclusions: Nursery biological risk factors can be used to predict the outcome. However the clinical picture is compound with various coexisting pathologies.